Bruce Bronzan Press Conference re Candidate for 31st Assembly District at Fresno Hilton Hotel - Watkins, Howard::::::::: (1982)
Bruce Bronzan speaking at lectern with media microphones: KMAK, 24, 30. KYNO.KFRE